Effect of rainfall on the compaction of dense-graded hot mix asphalt. (May 2019) - Ismail, S; Hassan, N A; Yaacob, H; Warid, M N M; Mashros, N; Mohamed, A; Hassan, S A; Azahar, N M
Abstract: Unpredictable tropical weather particularly rainfall can possibly interfere the compaction work of asphalt pavement. Heavy rainfall often leads the asphalt to cool and harden quickly and become difficult to compact. This study evaluates the effect of rainfall on the compaction properties of hot mix asphalt (HMA). A dense-graded mix of AC14 was prepared using 60/70 PEN bitumen and compacted at different temperatures. A handy steel roller was used to compact the slab samples with the size of 305 mm × 305 mm × 50 mm. The cooling rate and time available for compaction (TAC) were monitored using thermocouple under different levels of artificial rainfall and wind speed generated in the laboratory to simulate the wet conditions. The slabs were then cored at 100 mm diameter and tested for the volumetric properties. The result shows that environmental conditions and mix temperature determines the cooling rate and final density of the asphalt pavement. In addition, the TAC decreases as the compaction temperature reduces. Alternatively, working under light and moderate rainfall during the asphalt paving operation reasonably achieves the required degree of compaction (DOC). However, paving works under heavy rainfall reduce TAC, compactibility and density of the asphalt mat.